Sistem Informasi Geografis Kondisi Jalan di Kabupaten Sumedang Berbasis Android - Fathoni Mahardika; Dimitri Octaviana (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
Geographical Information System is an information system that has the ability to handle spatial data, including road conditions. Road data management has only been done conventionally. The platform used in building this geographic information system is based on Android. Android is chosen because Android is an open source that is easy to develop and the development of Android smartphones is already on the market today. The methodology used for this study is based on a prototype model. because this methodology uses modeling that is expected to facilitate the author in understanding the needs of users or users. The results of this study will present a geographic information system of road conditions in Sumedang Regency based on Android which was built using basic4android software combined with Jdk and SDK. The conclusion obtained is that this geographic information system can help the community service and water resources in managing road data and help the community to know the road conditions